Writing difficulties faced by novice writers - Saputra, Eko; Saputra, Dwi Bayu; Fadhli, Muhammad (UNIB Press, 2024)
Although there have been abundant literatures that discuss about students’ difficulties in academic writing, very few of them investigate the problems faced by novice writers. The present study aimed at investigating the difficulties experienced by the writers who did not have any prior academic trainings to write an English academic text. To this end, a total of 70 third-semester students from English department were assigned an open-ended questionnaire asking them to write any difficulties or problems they encountered while being asked to write an argumentative essay. Drawing on qualitative approach using thematic analysis, the findings show that the novice writers experienced 9 types of difficulties that were related to vocabulary, tenses, idea, sentence, topic, feeling of insecurity, grammar, time, and concept. Among those difficulties, vocabulary related one was found as the major problem that the novice writer experienced. The results suggested that academic writing is challenging for the inexperienced writers and having sufficient vocabulary size can be the prerequisite before taking academic writing course.